Paving the Way for Lignin Valorisation: Recent Advances in Bioengineering, Biorefining and Catalysis - Rinaldi, Roberto; Jastrzebski, Robin; Clough, Matthew T.; Ralph, John; Kennema, Marco; Bruijnincx, Pieter C. A.; Weckhuysen, Bert M. (Angewandte Chemie (International ed.), 2016)
Lignin is an abundant biopolymer with a high carbon content and high aromaticity. Despite its potential as a raw material for the fuel and chemical industries, lignin remains the most poorly utilised of the lignocellulosic biopolymers. Effective valorisation of lignin requires careful fine‐tuning of multiple “upstream” (i.e., lignin bioengineering, lignin isolation and “early‐stage catalytic conversion of lignin”) and “downstream” (i.e., lignin depolymerisation and upgrading) process stages, demanding input and understanding from a broad array of scientific disciplines. This review provides a “beginning‐to‐end” analysis of the recent advances reported in lignin valorisation. Particular emphasis is placed on the improved understanding of lignin's biosynthesis and structure, differences in structure and chemical bonding between native and technical lignins, emerging catalytic valorisation strategies, and the relationships between lignin structure and catalyst performance. Seeing the wood for the trees: Lignin is an abundant biopolymer with a high carbon content and high aromaticity. A critical analysis of “upstream” and “downstream” elements of lignin valorisation is given, including bioengineering, biorefining, and catalysis.